Exploring the cybersecurity landscape through cyber forensics - Husain, Mohd Shahid (IGI Global Scientific Publishing, 2025)
"This book delves into the intricacies of cyber forensics, offering insights and methodologies essential for uncovering and interpreting digital evidence in today's technologically advanced landscape"-- Provided by publisher